Presynaptic [Ca2+] and GCAPs: aspects on the structure and function of photoreceptor ribbon synapses - Schmitz, Frank (Frontiers in Molecular Neuroscience, 2014)
Changes in intracellular calcium ions [Ca2+] play important roles in photoreceptor signaling. Consequently, intracellular [Ca2+] levels need to be tightly controlled. In the light-sensitive outer segments (OS) of photoreceptors, Ca2+ regulates the activity of retinal guanylate cyclases thus playing a central role in phototransduction and light-adaptation by restoring light-induced decreases in cGMP. In the synaptic terminals, changes of intracellular Ca2+ trigger various aspects of neurotransmission. Photoreceptors employ tonically active ribbon synapses that encode light-induced, graded changes of membrane potential into modulation of continuous synaptic vesicle exocytosis. The active zones of ribbon synapses contain large electron-dense structures, synaptic ribbons, that are associated with large numbers of synaptic vesicles. Synaptic coding at ribbon synapses differs from synaptic coding at conventional (phasic) synapses. Recent studies revealed new insights how synaptic ribbons are involved in this process. This review focuses on the regulation of [Ca2+] in presynaptic photoreceptor terminals and on the function of a particular Ca2+-regulated protein, the neuronal calcium sensor protein GCAP2 (guanylate cyclase-activating protein-2) in the photoreceptor ribbon synapse. GCAP2, an EF-hand-containing protein plays multiple roles in the OS and in the photoreceptor synapse. In the OS, GCAP2 works as a Ca2+-sensor within a Ca2+-regulated feedback loop that adjusts cGMP levels. In the photoreceptor synapse, GCAP2 binds to RIBEYE, a component of synaptic ribbons, and mediates Ca2+-dependent plasticity at that site. Possible mechanisms are discussed.